\(y'=1-\dfrac{1}{\left(x+1\right)^2}=\dfrac{x^2+2x}{\left(x+1\right)^2}\)
Gọi đường thẳng d qua A có dạng: \(y=k\left(x-1\right)-1\)
d là tiếp tuyến của (C) \(\Rightarrow\left\{{}\begin{matrix}\dfrac{x^2+x+1}{x+1}=k\left(x-1\right)-1\\\dfrac{x^2+2x}{\left(x+1\right)^2}=k\end{matrix}\right.\) có nghiệm
\(\Rightarrow\dfrac{x^2+x+1}{x+1}=\dfrac{\left(x-1\right)\left(x^2+2x\right)}{\left(x+1\right)^2}-1\)
\(\Leftrightarrow\left(x+1\right)\left(x^2+x+1\right)=\left(x-1\right)\left(x^2+2x\right)-\left(x+1\right)^2\)
\(\Leftrightarrow x^2+3x+1=0\) \(\Rightarrow\left\{{}\begin{matrix}x_1=\dfrac{-3+\sqrt{5}}{2}\\x_2=\dfrac{-3-\sqrt{5}}{2}\end{matrix}\right.\)
\(\left(1-\dfrac{1}{\left(x_1+1\right)^2}\right)\left(1-\dfrac{1}{\left(x_2+1\right)^2}\right)=-1\Rightarrow\) hai tiếp tuyến kẻ từ A vuông góc nhau
Không thích tính toán thì từ \(x^2+3x+1=0\Rightarrow x^2+2x=-x-1\) thế vào \(y'=\dfrac{x^2+2x}{\left(x+1\right)^2}=\dfrac{-1}{x+1}\)
Do đó \(k_1k_2=-\dfrac{1}{x_1+1}.\left(-\dfrac{1}{x_2+1}\right)=\dfrac{1}{x_1x_2+x_1+x_2+1}=\dfrac{1}{1-3+1}=-1\)